Governing Disability in Austria: Reflections on a changing political field - Ursula Naue (Disability Studies Quarterly, 2006)
The Austrian Federal Act on the Equalization of Persons with Disabilities (BGStG), a law to facilitate equality, equal rights and opportunities for disabled people, passed the Austrian National Council (Nationalrat) in July 2005. The anti-discrimination law, which came into force at the beginning of 2006, marks the temporary peak of a long-lasting discussion on Austrian disability politics and policy. The debate on the draft and final version of the new law exemplifies the struggle of persons with disabilities against certain attitudes prevalent in the socio-political construction of disability. It also shows how disability policy in Austria has changed in recent years and how different political actors participate in shaping disability policy. This article discusses the problems concerning the actors, strategies and spaces of governing disability in Austria, as articulated in competing narratives that shape the field of disability policy.